2018
DOI: 10.1002/ptr.6237
|View full text |Cite
|
Sign up to set email alerts
|

L‐theanine ameliorate depressive‐like behavior in a chronic unpredictable mild stress rat model via modulating the monoamine levels in limbic–cortical–striatal–pallidal–thalamic‐circuit related brain regions

Abstract: L-theanine, originally found in green tea, elicits various physiological effects, such as promoting relaxation, improving concentration and learning ability, and providing antianxiety-like and antidepressant-like properties. This study aims to investigate the effects of L-theanine (2 mg/kg) on monoamine levels in an animal model of depression. The effect of L-theanine on the symptoms of depression was examined through the open-field test, sucrose preference test, and forced swim test. The monoamine neurotransm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…A recent study measured the effect of L-theanine (2 mg/kg) on 5-HT, NE and DA levels in an animal model of depression [111]. Measurements were taken in the limbic-cortical-striatal-pallidal-thalamic (LCSPT) circuit, which included the prefrontal cortex (PFC), nucleus accumbens (NAC), striatum (ST), amygdala, and hippocampus (HIP).…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study measured the effect of L-theanine (2 mg/kg) on 5-HT, NE and DA levels in an animal model of depression [111]. Measurements were taken in the limbic-cortical-striatal-pallidal-thalamic (LCSPT) circuit, which included the prefrontal cortex (PFC), nucleus accumbens (NAC), striatum (ST), amygdala, and hippocampus (HIP).…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…In the HIP, only DA levels significantly changed after theanine treatment. Despite the notable results, the authors were unable to identify the detailed signaling pathways responsible for the observed theanine-mediated improvements in monoamine neurotransmission [111].…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Studies have investigated the associations between L-theanine with dopamine and serotonin in rodents[51,59,60]. Yamada and colleagues have reported an increase of up to two-fold in dopamine levels induced by L-theanine perfusion in rat striatal brain[51].…”
mentioning
confidence: 99%
“…SPT was used to evaluate anhedonia-like behavior, which is a typical clinical manifestation of depressed patients. Locomotor activity in the OFT represents certain aspects of loss of interest, while the immobility time in FST and TST is taken as an index of behavioral despair in depression [17].…”
Section: Discussionmentioning
confidence: 99%